2000
DOI: 10.1002/1096-9896(2000)9999:9999<::aid-path708>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

An automated machine vision system for the histological grading of cervical intraepithelial neoplasia (CIN)

Abstract: The histological grading of cervical intraepithelial neoplasia (CIN) remains subjective, resulting in inter- and intra-observer variation and poor reproducibility in the grading of cervical lesions. This study has attempted to develop an objective grading system using automated machine vision. The architectural features of cervical squamous epithelium are quantitatively analysed using a combination of computerized digital image processing and Delaunay triangulation analysis; 230 images digitally captured from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
1
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(83 citation statements)
references
References 20 publications
2
78
1
2
Order By: Relevance
“…5-8, the first image of each row consists of the manual segmentation provided by our medical expert. 4 For each tissue image, the regions are labeled as either cancerous or normal and the boundary between these regions are drawn in red. In between these boundaries, there are also regions that can be included in either side without affecting the medical interpretation; such regions are shaded in red.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5-8, the first image of each row consists of the manual segmentation provided by our medical expert. 4 For each tissue image, the regions are labeled as either cancerous or normal and the boundary between these regions are drawn in red. In between these boundaries, there are also regions that can be included in either side without affecting the medical interpretation; such regions are shaded in red.…”
Section: Resultsmentioning
confidence: 99%
“…However, as it mainly relies on the visual interpretation, this examination may lead to a considerable amount of subjectivity, especially in cancer grading [1,2]. To reduce this subjectivity, it has been proposed to use computational methods that rely on the quantification of a tissue by defining mathematical features [3][4][5][6][7]. Although the very first step in this quantification is the segmentation of a tissue image into homogeneous regions, these studies have not mainly focused on this problem and have extracted features from the tissue image assuming that it is homogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…H&E-staining was used so that the results from image analysis could be directly compared and correlated with histopathologic assessment. Bahr 9 and Keenan et al 10 showed that data derived from H&E and Papanicolaou stains are linearly correlated with those from Feulgen.…”
Section: Karyometric and Statistical Analysesmentioning
confidence: 99%
“…Other issues are more specific to the application, such as the sampling, the type of staining, and the normalization issues. Recently, Keenan et al (9) found that quantitative analysis of cervical biopsy specimens stained with hematoxylin and eosin (H&E) could provide discriminant power to separate the different grades of dysplasia. The question then arises regarding the need for using Feulgen-stained specimen, which requires additional cutting and staining steps.…”
mentioning
confidence: 99%